An overlooked threatened species of eagle: Legge's Hawk Eagle Nisaetus kelaarti (Aves: Accipitriformes) - Gjershaug, J. O.; Diserud, O. H.; Rasmussen, P. C.; Warakagoda, D. (Zootaxa, 2008)
Species delimitation is fundamental to many areas of biology, and in cases where taxonomic status has not been sufficiently clarified the ramifications can be as serious as extinction due to the failure to implement conservation measures. Since 1931, the Mountain Hawk Eagle Nisaetus (Spizaetus) nipalensis Hodgson has included the allopatric Sri Lankan and southern Indian taxon N. kelaarti (Legge) as a subspecies, and its taxonomic status has not been re-evaluated. We found that N. kelaarti differs considerably from N. nipalensis in its relatively much larger bill and claws and short primary projection, and that it also differs consistently in numerous plumage characters and other mensural characters. Its vocalizations differ distinctly, and an earlier study found a moderate degree of genetic differentiation (4.4% in cyt b and 3.1% in CR) from N. nipalensis. The available evidence thus strongly and unambiguously supports the specific distinctness of N. kelaarti.